التكنولوجيا المالية في الصناعة المالية الإسلامية – الذكاء الاصطناعي نموذجا- - أوعيل، نعيمة (University of Eloued جامعة الوادي, 2025)
The financial sector is a primary driver of digital transformation. This research examines Islamic Financial Technology (FinTech) and the adoption of Artificial Intelligence (AI) within the Islamic financial industry. The findings show that while the Islamic financial sector and its use of FinTech are experiencing significant development, the application of AI remains limited. This is due to a few legal (Sharia), technical, and logistical challenges. Nevertheless, there is a growing recognition among institutions of the need to overcome these obstacles to foster the industry's continued growth and development.
FinTech in the Islamic Financial Industry – Artificial Intelligence as a Model -
مقال
Keywords: التكنولوجيا المالية الاسلامية; الصناعة المالية الاسلامية; الذكاء الاصطناعي; البنوك الاسلامية; Islamic financial technology; Islamic financial industry; Artificial intelligence; Islamic banks.